Numerical Simulation of Temperature Field in Ultra-Narrow Arc Welding of Thick-Walled Steam Turbine Valve Body Material - Ningnian, Gou; Yaowei, Wang; Shuo, Sun; Xiaotong, Han; M.S., Saffirna; XiaoXia, Jiang; Zhourong, Feng (International Journal of Integrated Engineering, 2022)
The welding problems of large and thick plates are becoming more prominent as the application of large-scale and thick-plate metal structures grows. Due to the issue of excessive welding deformation between the 60mm thick steam turbine valve body and the pipe joint, a new process method is employed to connect. In this paper, the welding technology of flux strip confined arc ultra-narrow gap is proposed to carry out welding test on the ZG13Cr9Mo2Co1NiVNbNB cast steel test block of steam turbine valve body material with a thickness of 60 mm. The welding temperature field is measured by means of a K-type thermocouple and numerical simulation. The results show that the thermal cycle curve obtained by the homogeneous body heat source simulation is basically consistent with the thermal cycle curve measured during the experiment, and the simulation results of the molten pool morphology are also consistent with the actual macroscopic morphology of the weld.